EFFECT OF SEASON ON SOME HAEMATOLOGICAL PARAMETERS OF THE ONE-HUMPED CAMEL (Camelus dromedariues) - S.O, Nawal; Osman, D.I.; Ali, M.A (Journal of Veterinary Medicine and Animal Production, 2022)
The effects of seasonal changes in the thermal environment on some haematological values of 100 camels have been investigated during dry summer, wet summer and winter for two years in United Arab Emirates. There were marked seasonal changes in ambient temperature and relative humidity. The count of the RBCs of the camel ranged from 3.7 to 9.1x 106 /ml, Hb percentage ranged from 4.1 to 11.9 %, packed cell volume (PCV) ranged from 12 % to 28 % and total WBCs count ranged from 5.5 to 15.9 x10 3 /ml depending on the season. The results indicated noticeable changes in most of the parameters investigated. The seasonal variation in RBCs count, PCV, Hb concentration and WBCs count were significant and the highest mean values of these parameters were obtained during winter. The histological structures of the blood cells were also studied. The shape of the RBCs was oval and non- nucleated. The WBCs are classified into two types, granulocytes and agranulocytes, based on the presence or absence of specific cytoplasmic granules. The three types of granulocytes (neutrophils, eosinophils and basophils) are named according to the staining reaction of their specific granules. The two types of agranulocytes (monocytes and lymphocytes) are devoid of specific cytoplasmic granules